INCREASING THE EFFECTIVENESS OF MARKETING MESSAGES THROUGH THE USE OF ATTRACTIVE SYNTAX (ANALYSIS OF THE EFFECT OF THE USE OF SURPRISE SYNTAX ON CONSUMER RESPONSE) - Fitrianti, Nida Garnida; Yolistina , Anggun; Fatmasari, Raden Roro (Yayasan Kreatif Indonesia Emas, 2024)
The use of surprising syntax in marketing messages has become a popular strategy to capture consumer attention and differentiate brands in a crowded marketplace. This research investigates the implications of the use of surprising syntax on brand image and consumer perceptions of the brand. We analyze how contextual factors such as demographics, psychographics, and culture influence the effectiveness of using surprising syntax in marketing messages. Through a comprehensive literature review, we explore the impact of using surprising syntax on brand image, consumer perceptions, and possible consumer responses. The results of the analysis show that the use of surprising syntax can help brands to stand out and create an impression of creativity, innovation and relevance. However, the use of surprising syntax can also carry the risk that if not done carefully, it can damage the brand image and affect consumers' perception of the brand. Therefore, it is important for marketers to consider the demographic, psychographic, and cultural characteristics of their target markets in designing marketing messages that use surprising syntax. With a careful approach and a focus on the overall brand experience, the use of surprising syntax can be an effective tool in strengthening brand image and building stronger relationships with consumers.